2018
DOI: 10.1093/scan/nsy059
|View full text |Cite
|
Sign up to set email alerts
|

Brain networks of happiness: dynamic functional connectivity among the default, cognitive and salience networks relates to subjective well-being

Abstract: Subjective well-being (SWB) reflects the cognitive and emotional evaluations of an individual’s life and plays an important role in individual’s success in health, work and social relationships. Although previous studies have revealed the spontaneous brain activity underlying SWB, little is known about the relationship between brain network interactions and SWB. The present study investigated the static and dynamic functional connectivity among large-scale brain networks during resting state functional magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 109 publications
3
42
0
1
Order By: Relevance
“…• cognitive (intellectual): the level of brain building (Kern et al, 2015) cognitive control, self-reflection (Shi, et al, 2018); consciousness (Iani et al, 2017), creative thinking (Mason et al, 2019;Kholodnaya, 2015), etc.…”
Section: Cognitive and Style Predictors Of The Students' Psychologicamentioning
confidence: 99%
See 2 more Smart Citations
“…• cognitive (intellectual): the level of brain building (Kern et al, 2015) cognitive control, self-reflection (Shi, et al, 2018); consciousness (Iani et al, 2017), creative thinking (Mason et al, 2019;Kholodnaya, 2015), etc.…”
Section: Cognitive and Style Predictors Of The Students' Psychologicamentioning
confidence: 99%
“…In a fifth place, "well-being" has a complex structure including cognitive and affective components. Despite the diversity of views on the structure of well-being (e.g., a newly introduced Seligman 's PERMA model includes five elements of psychological well-being: positive emotions, engagement, relationships, meaning, and achievement), it can be pointed out that the basic elements of the well-being are a person's cognitive and emotional assessment of life and its conditions (Kern et al, 2015;Shi, et al, 2018).…”
Section: Cognitive and Style Predictors Of The Students' Psychologicamentioning
confidence: 99%
See 1 more Smart Citation
“…Otaku consumers are considered especially good at this. Furthermore, Shi et al (2018) found that individuals with higher subjective well-being spend less time in a brain state in which information transfer between networks is less efficient, that is, indexed by weak connectivity between networks (default mode, frontal parietal, and saliency network). The importance of information flow between networks is consistent with the present finding that mindfulness revealed a positive correlation between daydreaming and well-being, as mindfulness enhances communication between brain networks (Brewer et al 2011).…”
Section: Theoretical Significancementioning
confidence: 99%
“…TPN dominance, measured by the mean lifetime of DMN/TPN dominance (i.e., the mean time a state lasts before transition to another state), indicating the persistence of DMN or TPN dominance3,45 ; the other metric comprised the number of dominance state transitions75,76 . Specifically, a 232-frame-long vector was derived by subtracting the TPN timeseries from the DMN timeseries for each subject.…”
mentioning
confidence: 99%